Management of Educator Recruitment in Improving the Quality of Education at Samarinda Catholic Elementary School - Theresia Ping; Warman Warman; Laili Komariyah (PT ARRUS Intelektual Indonesia, 2022)
This study aims to describe the implementation of the recruitment of educators to improve the quality of education in the Samarinda City Catholic Elementary School. A qualitative approach with a description method is used in this study. The data collection involved five key informants, namely the head of the foundation, staffing staff, school principals, and vice principals in the field of curriculum, and one supporting informant. Collecting research data using the method of observation, documentation, and interviews. The process of data analysis is carried out through the stages of reduction, presentation, and drawing conclusions. The results of this study indicate that the implementation of recruitment is based on data analysis of teacher needs and standard operating procedures consisting of the delivery of recruitment information through teachers or employees and alumni, acceptance of applications, file selection, summoning applicants for interview tests, and announcements made transparently. The findings in this study have managerial implications. The implications of the management of the recruitment of educators on improving the quality of education are planning, implementation, and supervision activities that support each other in an effort to achieve goals. The mutually supportive relationship of the management function that has contributed to the achievement of goals is shown by the existence of step-by-step stages that become a common reference in an effort to get educators as expected